Compressive Strength and Microstructural of Palm Oil Fuel Ash-Fly Ash Based Geopolymer Mortar. Issue 1 (February 2021) - Humaedi, Muhammad Dwi Caesar; Saloma,; Hanafiah,; Iqbal, Maulid M.
Abstract: The infrastructure develops very rapidly, along with the increase of market demand for cement, but there is a problem of cement production. Cement production can produce hazardous wastes of CO2 . CO2 can cause greenhouse effect. The amount of CO2 produced by cement production is equal to the amount of cement produced. To overcome these problems, it needed to look for alternative materials for cement substitution. Geopolymer is an alternative material that can be a replacement or substitution for cement. Geopolymer can reduce CO2 wastes generated by cement production and also can reduce industrial generated waste such as fly ash and palm oil fuel ash. In the manufacturing of geopolymer, this study used fly ash and palm oil fuel ash acting as precursor and also Na2 SiO3 and NaOH as activator solution. This study aimed to examine the effects of the ratio of alkali activator in this case is Na2 SiO3 and NaOH to microstructure of geopolymer mortar with fly ash and palm oil fuel ash precursor. This study used a variation of 75%:25%, 50%:50%, 25%:75% precursor compositions and variation of alkali activator ratios of 1.5, 2.0, and 2.5. This study used the concentration of NaOH of 14 M. The results showed that along with the increase in concentration of Na2 SiO3 and NaOH, the structure seen on the mortar becomes denser and the greater fly ash content in the mortar precursor mixture the structure also become denser.